Current Concepts in Hip Preservation Surgery: Part I. (November 2015) - Adler, Kelly L.; Cook, P. Christopher; Yen, Yi-Meng; Giordano, Brian D.
Context: An evolution in conceptual understanding, coupled with technical innovations, has enabled hip preservation surgeons to address complex pathomorphologies about the hip joint to reduce pain, optimize function, and potentially increase the longevity of the native hip joint. Technical aspects of hip preservation surgeries are diverse and range from isolated arthroscopic or open procedures to hybrid procedures that combine the advantages of arthroscopy with open surgical dislocation, pelvic and/or proximal femoral osteotomy, and biologic treatments for cartilage restoration. Evidence Acquisition: PubMed and CINAHL databases were searched to identify relevant scientific and review articles from January 1920 to January 2015 using the search terms hip preservation, labrum, surgical dislocation, femoroacetabular impingement, peri-acetabular osteotomy, and rotational osteotomy . Reference lists of included articles were reviewed to locate additional references of interest. Study Design: Clinical review. Level of Evidence: Level 4. Results: Thoughtful individualized surgical procedures are available to optimize the femoroacetabular joint in the presence of hip dysfunction. Conclusion: A comprehensive understanding of the relationship between femoral and pelvic orientation, morphology, and the development of intra-articular abnormalities is necessary to formulate a patient-specific approach to treatment with potential for a successful long-term result.